Policy changes leaving marks on the economy - Geraldine Dany-Knedlik; Guido Baldi; Nina Maria Brehl; Hella Engerer; Angelina Hackmann; Pia Hüttl; Konstantin Kholodilin; Frederik Kurcz; Laura Pagenhardt; Jan-Christopher Scherer; Teresa Schildmann; Hannah Magdalena Seidl; et al. (DIW Weekly Report, 2025)
The German economy is stuck in a period of stagnation: Following two years of consecutive slight declines in GDP, growth is not expected for 2025 either. Weak exports, rising unemployment worries, and the resulting reserved private consumption and economic policy uncertainty are slowing the economy. Structural adjustment processes and the erratic trade policy of the Trump administration are weighing on German industry. A recovery, albeit gradual, is not expected until the summer. Once a government is formed, the economic policy framework will be clearer, the labor market will stabilize, and private consumption will pick up speed a little. Further interest rate cuts by the European Central Bank should support investment. In addition, the prospective upcoming government coalition of the CDU/CSU and the SPD has agreed on a special fund for infrastructure. Without this fund, the German economy is projected to grow by 1.1 percent in 2026, and with the fund, growth is expected to be a good two percent. The global economy has largely stayed on course so far, although current US trade policy is leaving noticeable marks. Despite this, global economic output is unlikely to grow less than in 2024, with 3.5-percent growth in 2025 and 3.6-percent growth in 2026.
Keywords: E32; E66; F01; 330; Business cycle forecast; economic outlook